Transición demográfica y sus implicaciones en la salud pública - Caraguay Salinas, Paul Fabian (Machala : Universidad Técnica de Machala, 2019)
The demographic transition is taking place all over the world, this transition translates into an increase in life expectancy, we see demographic transition in the developing countries, it becomes more important due to its context within the planning of public spending for the implementation of health policies and programs, currently there are around 600 million people over 60 years of age in the world. The region must face the challenge posed by the enormous increase in the proportion of the population aged 60 and over that goes from 8% in the year 2000 to 14.1% in the year 2025. This accelerated aging of the world population will increase the demands and modify the orientation and the budget of the health policies and programs. Objective: To update the scientific advances obtained on the demographic transition and its implications in public policies and health programs. Methods: Analysis of the information obtained through search engines of biomedical research, such as: PubMed, Scielo, The Lancet, Sanitary Gazette; In addition, the decennial health plan of the Metropolitan District of Quito, the National Health and Nutrition Survey - ENSANUT, the report of the Economic Commission for Latin America and the Caribbean - ECLAC. Conclusion: After the selection of 11 articles and important information, it is concluded in this review that the demographic transition is a fundamental factor that should be analyzed for the execution of planning projects, and its subsequent process of financing and execution of policies, programs and public health projects.
La transición demográfica se está produciendo en todo el mundo, esta transición se traduce en el aumento de la esperanza de vida, vemos como en los países en desarrollo la transición demográfica, toma mayor importancia por su contexto dentro de la planificación en el gasto público para la ejecución de las políticas y programas de salud, actualmente hay en el mundo unos 600 millones de personas mayores de 60 años, La región debe enfrentar el reto que plantea el enorme aumento de la proporción de población de 60 años y más, que pasa de 8 % en el año 2000 a 14.1 % en el año 2025. Este envejecimiento acelerado de la población mundial aumentara las demandas y modificara la orientación y el presupuesto de las políticas y programas de salud. Objetivo: Actualizar los avances científicos obtenidos sobre la transición demográfica y sus implicaciones en las políticas públicas y programas de salud. Métodos: Análisis de la información obtenida a través de motores de búsqueda de investigación biomédica, como: PubMed, Scielo, The Lancet, Gaceta Sanitaria; además la Encuesta Nacional de Salud y Nutrición – ENSANUT, el informe de la Comisión Económica para América Latina y el Caribe - CEPAL. Conclusión: Luego de la selección de 11 artículos e información importante se concluye en esta revisión que la transición demográfica es un factor fundamental que debería analizarse para la ejecución de proyectos de planificación, y su posterior proceso de financiamiento y ejecución de las políticas, programas y proyectos de salud pública.
Keywords: TRANSICION; DEMOGRAFIA; SALUD PUBLICA